IMPLEMENTASI TEORI VIKTIMOLOGI PADA HUKUM PIDANA INDONESIA - Rumapea, Mazmur Septian; Sari, Defitrie Nathania; Sijabat, Jecyka Cklaudya; Putri, Twinkle Suwarna (Universitas Muhammadiyah Ponorogo, 2023)
Victimology is a research or insight related to victims and their elements, which is a derivative of criminology. The main point related is the impact of a crime that causes victims and suffers losses. The purpose of this study is to find out about the regulation of the theory of victimology in Indonesian criminal law and to find out its implementation. This study uses a qualitative self-research procedure. This research is described descriptively and directed using data source analysis. In this research the collection of information used is secondary data, in which the data comes from various collections of journals. The results of the research show that the regulation of victimology in Indonesian Criminal Law regarding the protection of victims is still universal because it has been stated in various laws. Also the implementation of victimology in Indonesian Criminal Law has been well implemented, although it has not been realized as it should be as regulated in Indonesian law.